MESENCHYMAL STEM CELLS: AN INNOVATIVE APPROACH IN PHARMACOKINETICS - Tripathy, Seema; Mohanty, Prafulla Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Multipotent mesenchymal stem cells (MSCs) are special kind of stem cells which originate from mesenchyme. These cells can be used as an imperative tool to study reproductive toxicity, carcinogenicity, mutagenicity, genotoxicity, and pharmacokinetics. This novel system may reveal toxicantinduced etiology, decipher detailed understanding on molecular mechanisms of toxicants induced pathways and also enumerate the safe dose of an investigational product. Hence, this could ultimately replace, improve or overtake current predictive models in toxicology. The particular review describes the utilization of MSCs in different field of toxicological and pharmacological research. Keywords: Mesenchymal stem cells, Toxicant, Etiology, Pharmacokinetics.